2019
DOI: 10.1111/his.13768
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between renal CD68+ infiltrates and the Oxford Classification of IgA nephropathy

Abstract: Aims The Oxford Classification E score (endocapillary hypercellularity) predicts renal functional decline in IgA nephropathy (IgAN) patients free from steroid/immunosuppressive (IS) therapy, but is poorly reproducible. We hypothesise that endocapillary hypercellularity reflects glomerular inflammation and that the presence of CD68‐positive cells is a more robust marker of E score. Methods and results CD68‐positive cells were quantified in glomeruli and tubulointerstitium in biopsies from 118 IgAN patients, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 24 publications
2
42
2
Order By: Relevance
“…Our result was consistent with this previous study. Their subsequent study showed that CD68 infiltrates were associated with E score, suggesting that the pathogenesis of more severe proteinuria in patients with E score was correlated with renal inflammation [25]. They also reported a significant association between E and C scores.…”
Section: Discussionmentioning
confidence: 93%
“…Our result was consistent with this previous study. Their subsequent study showed that CD68 infiltrates were associated with E score, suggesting that the pathogenesis of more severe proteinuria in patients with E score was correlated with renal inflammation [25]. They also reported a significant association between E and C scores.…”
Section: Discussionmentioning
confidence: 93%
“…Recently the reproducibility of the E score between pathologists has been questioned. [ 5 ] Bellur et al . in their study reported that the reproducibility for endocapillary hypercellularity and mesangial proliferation between local and central pathologists was poor.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant immunoexpression of CD68 in non-human myeloid-derived cells is more frequent for clones KP1 and EBM11 in cryostat sections in comparison to the clone PG-M1 which was used by Soares et al . [ 5 ] to assess the E score. However, in our study cytoplasmic positivity for CD 68 was recorded strictly in an endocapillary lumen in mononuclear cells with histomorphological characteristics of macrophage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunostaining for lysozyme, S100A9 and CD68 was performed on individual tissue sections. Positively stained cells within the glomerular capillary tuft were manually counted using criteria described by Soares et al 53 . A positive cell was defined by clearly delimited aggregates of brown-stained cytoplasmic granules with or without a juxtaposed nucleus.…”
Section: Statistical Analysis Lc-msmentioning
confidence: 99%